1968
DOI: 10.1161/01.cir.38.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Thyroid State on Myocardial Contractility and Ventricular Ejection Rate in Man

Abstract: Although the circulatory changes in various thyroid states are well known, the alterations of myocardial contractility of hypothyroidism and hyperthyroidism have remained controversial. The changes in the length of the ejection time (ET) and isovolumic contraction time (ICT) are used as indicative of alterations in inotropic state of the myocardium. Isovolumic contraction time, ejection time, and pre-ejection period were measured externally in 10 normal, 13 hyperthyroid, and five hypothyroid subjects. Cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
8

Year Published

1972
1972
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(44 citation statements)
references
References 25 publications
3
33
0
8
Order By: Relevance
“…44, No. 1, JANUARY 1979 the same results in the dog, and similar responses have been found in hyperthyroid human subjects (Amidi et al, 1968;Grossman et al, 1971).…”
Section: Effects Of Thyrotoxicosis On Myocardialsupporting
confidence: 76%
See 1 more Smart Citation
“…44, No. 1, JANUARY 1979 the same results in the dog, and similar responses have been found in hyperthyroid human subjects (Amidi et al, 1968;Grossman et al, 1971).…”
Section: Effects Of Thyrotoxicosis On Myocardialsupporting
confidence: 76%
“…absolute heart weight usually is normal or only slightly increased in chronic experiments on animals (Taylor et al, 1969) and in man with uncomplicated thyroid hyperfunction (Friedberg and Sohval, 1937). Nevertheless, the speed of contraction is increased and the time of tension development is shortened in both early (Buccino et al, 1967;Pannier, 1968;Korecky and Beznak, 1971;Murayama and Goodkind, 1968) and well established thyrotoxicosis (Taylor et al, 1969;Amidi et al, 1968;Grossman et al, 1971). Clinical experience suggests that cardiac function may be maintained at above normal levels for many years, unless there is advanced age or coincident cardiac disease (Hurxthal, 1940;Sandier and Wilson, 1959).…”
Section: Effects Of Thyrotoxicosis On Myocardialmentioning
confidence: 99%
“…The "myxedema heart" was first described by Zondek (6), who noted a dilated cardiac silhouette, slow indolent heart action, and low electrocardiographic voltage, which were all corrected by thyroid hormone therapy. Although invasive (7) and noninvasive (8) studies have since confirmed that thyroid hormone deficiency is associated with a reversible decrease in myocardial contractility, it has remained controversial whether hypothyroidism alone can cause a dilated cardiomyopathy and clinical heart failure. Furthermore, although effects of thyroid hormones on myocardial myosin isoenzyme expression (9,10), 3-adrenergic receptor number (11), sarcoplasmic reticulum calcium exchange (12), and guanine nucleotide-binding regulatory proteins (13) have all been described in experimental animals, the fundamental pathogenesis of myocardial dysfunction caused by thyroid hormone deficiency in humans has remained uncertain.…”
mentioning
confidence: 99%
“…Com o progresso nos estudos não-invasivos da função miocárdica em humanos, foram demonstradas alterações nos intervalos sistólicos em pacientes com hipo e hipertireoidismo, e a reversão dessas alterações após a normalização dos níveis de HT séricos (84)(85)(86)(87). Especialmente interessante, os intervalos dos tempos sistólicos se mostraram acurados em diferenciar pacientes hipo, eu e hipertireóideos (85).…”
Section: Sistema Cardiovascularunclassified
“…Esse último é definido como o período entre o fechamento da valva mitral e a abertura da valva aórtica (88). O período pré-ejetivo também inclui o retardo eletromecânico, e foi usado mais freqüentemente quando os métodos empregados para medir os intervalos sistólicos incluíam a fonocardiografia (85)(86)(87)89).…”
Section: Sistema Cardiovascularunclassified